Variation in growth and developmental responses to supraoptimal temperatures near latitudinal range limits of gypsy moth Lymantria dispar (L.), an expanding invasive species. (27th March 2017) - Thompson, Lily M.; Faske, Trevor M.; Banahene, Nana; Grim, Dominique; Agosta, Salvatore J.; Parry, Dylan; Tobin, Patrick C.; Johnson, Derek M.; Grayson, Kristine L.
Abstract: Variation in thermal performance within and between populations provides the potential for adaptive responses to increasing temperatures associated with climate change. Organisms experiencing temperatures above their optimum on a thermal performance curve exhibit rapid declines in function and these supraoptimal temperatures can be a critical physiological component of range limits. The gypsy moth, Lymantria dispar (L.) (Lepidoptera: Erebidae), is one of the best‐documented biological invasions and factors driving its spatial spread are of significant ecological and economic interest. The present study examines gypsy moth sourced from different latitudes across its North American range for sensitivity to high temperature in constant temperature growth chamber experiments. Supraoptimal temperatures result in higher mortality in northern populations compared with populations from the southern range extent (West Virginia and coastal plain of Virginia, U.S.A.). Sublethal effects of high temperature on traits associated with fitness, such as smaller pupal mass, are apparent in northern and West Virginia populations. Overall, the results indicate that populations near the southern limits of the range are less sensitive to high temperatures than northern populations from the established range. However, southern populations are lower performing overall, based on pupal mass and development time, relative to northern populations. This suggests that there may be a trade‐off associated with decreased heat sensitivity in gypsy moth. Understanding how species adapt to thermal limits and possible fitness trade‐offs of heat tolerance represents an important step toward predicting climatically driven changes in species ranges, which is a particularly critical consideration in conservation and invasion ecology.